2020
DOI: 10.3390/ma13020456
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of Novel Sodium Silicate Microcapsule-Based Self-Healing Oil Well Cement

Abstract: A majority of well integrity problems originate from cracks of oil well cement. To address the crack issues, bespoke sodium silicate microcapsules were used in this study for introducing autonomous crack healing ability to oil well cement under high-temperature service conditions at 80 °C. Two types of sodium silicate microcapsule, which differed in their polyurea shell properties, were first evaluated on their suitability for use under the high temperature of 80 °C in the wellbore. Both types of microcapsules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 29 publications
2
19
0
1
Order By: Relevance
“…At present, the shells of microcapsules are usually chemically synthesized from thermosetting resins (polyurethane, urea-formaldehyde, melamine-formaldehyde, etc.) by in-situ polymerization or interfacial polymerization [ 24 , 25 , 26 ]. These microcapsules easily maintain integrity during concrete mixing and forming (the shell material has high strength), but they also increase the difficulty of breaking and releasing the healing agent under stress [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the shells of microcapsules are usually chemically synthesized from thermosetting resins (polyurethane, urea-formaldehyde, melamine-formaldehyde, etc.) by in-situ polymerization or interfacial polymerization [ 24 , 25 , 26 ]. These microcapsules easily maintain integrity during concrete mixing and forming (the shell material has high strength), but they also increase the difficulty of breaking and releasing the healing agent under stress [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies that use sodium silicate as a self-healing agent include this product encapsulated, so it reacts after being released out of a microcapsule (20). Microencapsulated sodium silicate has displayed positive impact, healing cracks up to 0.20 mm (75), improving water impermeability through sorptivity (76), and promoting mechanical recovery (21). However, increasing the content of microcapsules can decrease compressive strength (76) because of the increase in porosity.…”
Section: Inorganic Chemical Agentsmentioning
confidence: 99%
“…Glass 35 Tubular (Van Tittelboom et al 2011a, 2011bEscobar et al 2013;Tsangouri et al 2013aTsangouri et al , 2013bTsangouri et al , 2013cTsangouri et al , 2014Tsangouri et al , 2015Tsangouri et al , 2019Maes et al 2014;Van Tittelboom et al 2014;Feiteira et al 2014Feiteira et al , 2016aFeiteira et al , 2016bVan Belleghem et al 2015, 2018cKanellopoulos et al 2015;Qureshi et al 2016;Heede et al 2016;Karaiskos et al 2016;Restuccia et al 2017;Anbarlouie et al 2018;Van Mullem et al 2018;Hu et al 2018;Wu et al 2019;Mao et al 2020) UF-PU-PUrea 29 Spherical (Dong et al 2012(Dong et al , 2016(Dong et al , 2017Wang et al 2013Wang et al , 2017Wang et al , 2018Wang et al , 2019Wang et al , 2020Song et al 2013;Litina et al 2014;Gilford et al 2014;Mostavi et al 2015;Zhou et al 2015;Li et al 2016bLi et al , 2017Li et al , 2020aTan et al 2016;…”
Section: Shell Materials Number Of Papers Geometry Referencesunclassified
“…Polyurea, ureaformaldehyde, and polyurethane is a group of polymers that have been studied as shell materials, providing an extensive feedback on the triggering mechanism and the adhesion strength with cement matrix. Due to the high thermal stability, polyurea was used for the preparation of microcapsules for oil well cement (Mao et al 2020). The examination of specimens with embedded microcapsules in SEM indicated that the microcapsules were broken, and the shells were not detached from the matrix, suggesting good bonding.…”
Section: Triggering Mechanismmentioning
confidence: 99%